2011
DOI: 10.1002/lary.21860
|View full text |Cite
|
Sign up to set email alerts
|

Bell's palsy during pregnancy: Is it associated with adverse perinatal outcome?

Abstract: Chronic hypertension and obesity are independent risk factors for Bell's palsy. Bell's palsy during pregnancy is significantly associated with severe preeclampsia. Nevertheless, no significant association exists between Bell's palsy and adverse perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 15 publications
4
40
1
6
Order By: Relevance
“…In a study of pregnant women, of 242,000 deliveries, 0.17% of expectant mothers were diagnosed with Bell's palsy. 16 Obesity, chronic hypertension, and severe preeclampsia also increased the risk. Diabetes is also a risk factor, and hypertension may be independently associated with an increased risk of Bell's palsy.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of pregnant women, of 242,000 deliveries, 0.17% of expectant mothers were diagnosed with Bell's palsy. 16 Obesity, chronic hypertension, and severe preeclampsia also increased the risk. Diabetes is also a risk factor, and hypertension may be independently associated with an increased risk of Bell's palsy.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that obesity as well as chronic hypertension were independent risk factors for Bell's palsy during pregnancy; however, no significant correlation could be found between facial paralysis and adverse perinatal outcomes. 7 Furthermore, it has even been suggested that Bell's palsy could be a predictor of PE. 4 HELLP syndrome, 8 which was present in case 1, has not been previously reported in association with Bell's palsy occurring during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…51,54 Most cases of Bell palsy occur in the third trimester (71% to 89.5%), followed by 9.8% to 21.3% in the puerperium, 5.3% in the first trimester, and 2.4% to 2.6% in the second trimester. 49,51,55,56 Controversy exists as to the causative mechanism for Bell palsy in pregnancy, and why it is essentially limited to the third trimester and puerperium. In the general population, speculative causative agents include viral infection, vascular ischemia, autoimmune inflammatory disorders, and hereditary factors.…”
Section: Bell Palsy In Pregnancymentioning
confidence: 98%
“…49 It is acute in onset, unilateral, and is considered to be idiopathic. 50 It occurs in 17 to 25 of 100,000 people annually, equally in males and females, with no predilection for a particular side of the face.…”
Section: Bell Palsy In Pregnancymentioning
confidence: 99%